Answer :

(i) We know, 2 sin A cos B = sin(A + B) + sin(A – B)


2 sin 3x cos x = sin (3x + x) + sin (3x – x)


= sin (4x) + sin (2x)


= sin 4x + sin 2x


(ii) We know, 2 cos A sin B = sin (A + B) – sin (A – B)


2 cos 3x sin 2x = sin (3x + 2x) – sin (3x – 2x)


= sin (5x) – sin (x)


= sin 5x – sin x


(iii) We know, 2 sin A sin B = cos (A – B) – cos (A + B)


2 sin 4x sin 3x = cos (4x – 3x) – cos (4x + 3x)


= cos (x) – cos (7x)


= cos x – cos 7x


(iv) We know, 2 cos A cos B = cos (A + B) + cos (A – B)


2 sin 3x cos x = cos (7x + 3x) + cos (7x – 3x)


= cos (10x) + cos (4x)


= cos 10x + cos 4x


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Prove that :
<
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Prove that :
<
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics